2003
DOI: 10.1177/154405910308200513
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloid Receptor Expression in the Rat Tongue and Palate

Abstract: Capsaicin, the pungent substance in hot peppers, evokes a sensation of burning pain by stimulating the vanilloid receptor 1 (VR1) on primary afferent neurons. Immunohistochemistry revealed that the taste papillae in the tongue and palate are richly innervated by VR1-immunoreactive nerve fibers. Furthermore, VR1 protein expression was seen in the epithelium facing the oral cavity, although taste cells seemed to be devoid of VR1. The most conspicuous VR1 expression was observed in the epithelial cells of the pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 15 publications
(15 reference statements)
3
55
1
Order By: Relevance
“…The fungiform papillae are rich in TRPV1-immunostained fibers, which are localized around the taste buds, and some of these fibers actually enter taste buds. Most TRPV1 fibers show immunoreactivity for substance P, while approximately half of the TRPV1 fibers are positive for calcitonin gene-related peptide (14,18,21). It has been reported that the neuropeptides CCK and substance P increase rat CT responses to NaCl (13).…”
Section: Possible Interactions Between Trpv1/trpv1t and Trpm5mentioning
confidence: 99%
See 1 more Smart Citation
“…The fungiform papillae are rich in TRPV1-immunostained fibers, which are localized around the taste buds, and some of these fibers actually enter taste buds. Most TRPV1 fibers show immunoreactivity for substance P, while approximately half of the TRPV1 fibers are positive for calcitonin gene-related peptide (14,18,21). It has been reported that the neuropeptides CCK and substance P increase rat CT responses to NaCl (13).…”
Section: Possible Interactions Between Trpv1/trpv1t and Trpm5mentioning
confidence: 99%
“…Several agonists and antagonists of TRPV1 modulate the Bz-insensitive NaCl CT responses in animal models and alter human salt taste (11, 20, 26 -30, 40, 41, 48). TRPV1 expression has been observed immunohistochemically in primary afferents and also in oral epithelial cells in the rat tongue (18,21) and in human taste cell lines from lingual epithelium by RT-PCR (16,17). A recent study identified TRPV1 rs8065080 (C Ͼ T) singlenucleotide polymorphism as a likely modifier of an individual's perception of salt at suprathreshold levels (12).…”
mentioning
confidence: 99%
“…In the urinary bladder, TRPV1 channels are present in both sensory nerves and the bladder epithelium, in which they contribute to voiding behavior (Birder et al, 2001(Birder et al, , 2002. Interestingly, in the tongue, TRPV1-positive fibers innervate the taste papillae (Ishida et al, 2002;Kido et al, 2003), and amiloride-insensitive salt responses in the chorda tympani are abolished in TRPV1-null animals (Lyall et al, 2004). Thus, TRPV1 or a splice variant may transduce some forms of salt taste perception.…”
Section: Trpv1 May Transduce Nociceptive Responses To Elevated Ionic mentioning
confidence: 99%
“…20) The fact that an intragastric administration of capsiate via a stomach tube increased the energy expenditure in mice provides additional evidence for the oral cavity not being a target of capsinoids to enhance the energy expenditure. 12) There are TRPV1-immunoreactive nerve fibers in both the stomach and small intestine, 21) and almost all these fibers in the small intestine are thought to be derived from extrinsic nerves (spinal and vagus nerves).…”
mentioning
confidence: 99%